Risk of upper aerodigestive tract cancers in a case-cohort study of autoworkers exposed to metalworking fluids. Issue 5 (16th April 2004) - Zeka, A; Eisen, E A; Kriebel, D; Gore, R; Wegman, D H
Abstract : Aims: To re-examine aerodigestive cancer risk in a cohort of autoworkers exposed to metal working fluids (MWF), using improved case definition and more recently diagnosed cases. Methods: The autoworker cohort included 31 100 hourly workers alive on 1 January 1985 who worked at three automobile plants in Michigan. A case-cohort design was carried out that included incident cases of cancers of the larynx, oesophagus, and stomach, and a 10% sample of the cohort. A Cox proportional hazards model was used to estimate MWF exposure effects. The smoothing method of penalised splines was used to explore the shape of the underlying exposure-response curves. Results: The most important finding was the association between larynx cancer incidence and cumulative straight MWF exposure. The results for oesophageal cancer were less consistent. For stomach cancer there was no evidence of excess risk. Conclusion: This association between larynx cancer and straight MWF exposures was consistent with a previous finding in this cohort, providing further support for a causal relation.